Predicting Online Sales: A Machine Learning Approach for Sales Forecasting in Online Platform - V Rajeshkumar Pitani, Harsh Lohiya (Mathematical Statistician and Engineering Applications, 2022)
There are very few opportunities left for traditional merchants to grow their revenue through increasing sales as a result of increased sales because online shopping has become such a significant sector in the modern period. It is possible to utilise an algorithm that makes use of machine learning to create predictions regarding the kind of products that ought to be offered during a particular month in order to increase sales overall. When the forecast has been finished, a dashboard will be developed to illustrate which products should have been sold in order to obtain high amounts of revenue. This will be done so that the prediction can be validated. It has been identified how to bill for the sales, and an expert's support was utilised in conducting the analysis. However, in this predicament, not everyone possesses the resources necessary to consult with professionals who are able to aid them. For sellers, experience is an essential qualification to have. People who have only been operating their businesses for a couple of years have very little to no experience and are looking for support. The process of making accurate projections regarding future product sales is a crucial part of effective purchase management. The unpredictability, global scope, and ever-changing nature of the commercial environment in which businesses must compete is one of the most critical challenges that companies must face in today's world. Because customers' expectations about pricing and quality are always expanding, modern manufacturers “can no longer rely only on the cost advantage that they have over their competitors. This is because customers' expectations are consistently becoming more demanding. It is vital to forecast sales in order to maintain suitable inventory stock levels. Estimating the exact future demand for goods has been a constant challenge for firms in all different types of industries”. There is a chance that the overall profit will be put in jeopardy if the commodities are difficult to obtain or if there is an excess of goods available compared to the amount of demand for them.